Personal development in secondary education: the Irish Transition Year - Clerkin, Aidan (Education Policy Analysis Archives, 2012)
Secondary education in Ireland includes an optional Transition Year (TY) between the junior and senior examination cycles, when students are typically about 15 years old. Transition Year is an innovative programme, unique to Irish education, which is intended as a non-academic year devoted to personal and social development in the absence of examination pressure. Slightly more than half of the eligible student cohort take part in the programme, with the remainder skipping TY and progressing directly to senior education. Qualitative evidence suggests that TY is generally viewed as a positive experience for students, although competing perspectives regard the programme as a luxury that is no longer worth sustaining. This article discusses the development of the programme and its relevance to the Irish education system, reviews previous and related research, and identifies future directions and areas where further attention is warranted.